Characterization and utilization of bamboo (Dendrocalamus Latiflorus) shoot powder - Rotas, Irene Rusia (2010.)
The study involved the characterization and utilization of bamboo shoot powder from dalusan (Dendrocalamus latiflorus)
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Bamboo shoot; Dalusan--Dendrocalamus latiflorus